Behavioral explanation for educational health and mortality differentials in Austria - Franz Schwarz (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2006)
The present study examines the health behavior of more than 30,000 individuals aged 25-74 in Austria, using education as an indicator of socioeconomic status. Of particular interest is the magnitude of the educational disparities in health behavior between hypothetical most and least educated, measured by the Relative Index of Inequality. The findings show that education has a great positive impact on the extent to which a person lives a healthy lifestyle with regard to diet, physical activity, and smoking. Furthermore, the prevalence of overweight decreases significantly with any increase in education, and people with more education are also much more likely to get their periodical vaccinations.
Keywords: 300; Health behavior; Lifestyle; Education; Socioeconomic; Differentials; Inequalities; Austria; Gesundheitsvorsorge; Sterblichkeit; Bildungsniveau; Sozialer Status; Österreich